Electrochemical Properties of the Nanoporous Carbon/Aprotic Electrolyte System - B.K.В Ostafiychuk; I.M.В Budzulyak; B.I.В Rachiy; R.P.В Lisovsky; V.I.В Mandzyuk; P.I.В Kolkovsky; R.I.В Merena; M.V.В Berkeshchuk; L.V.В Golovko (Журнал нано- та електронної фізики)
The paper describes researches of the behaviour of capacitor systems based on the nanoporous carbon in aprotic electrolytes. Carbon material have been obtained by carbonization of fruit seeds and used for the formation of electrodes of electrical storage devices. Much attention is paid to research of the structural characteristics of carbon using the isothermal nitrogen adsorption method. The purpose of the research is establishing of regularities of electrochemical processes at the electrode/electrolyte interface versus high surface area of carbon material, which formed by choice of technological parameters of obtaining and modification, as well as the type of aprotic electrolyte used.